Cinnamon essential oil synergizes with sodium hypochlorite to suppress VBNC formation in Escherichia coli O157:H7 by modulating the temporal expression of arcA/relA-associated stress regulators - Haoqing Zhao; Zongwei Bai; Jingfeng Zhang; Yamei Chen; Huiting Huang; Xiaoxuan Wang; Jiawen Sun; Lei Shi; Xiaoli Xu; Lichao Zhao (Food Microbiology, 2027)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Fecal pollution source tracking at a marine bathing beach: A case study of Beihai Silver Beach - Hongxia Ming; Ziqi Chen; Tingting Shi; Zhongzhi Chen; Wenjing Pan; Jiannan Lin; Jie Su; Jingfeng Fan (Regional Studies in Marine Science, 2026)

Respiration‐Induced Weakening of Land Sink Contributed to the Largest CO 2 Increase in 2024 - Chaoya Dang; Zihua Shi; Josep Peñuelas; Philippe Ciais; Stephen Sitch; Jingfeng Xiao; Xing Li; Yanfeng Ding; Songhan Wang (Global Change Biology, 2026)
In 2024, the global annual growth rate of atmospheric CO 2 (CGR) surged to a record of 3.73 ppm year −1 —the highest since 1959—exceeding the 1.5°C climate threshold for the first time. However, the drivers behind this unprecedented rise remain poorly understood. Here, we employed a machine‐learning approach integrating satellite‐derived gross primary productivity (GPP) and climatic data to estimate the 2024 land sink (S LAND ) at approximately 2.21 ± 0.25 GtC year −1 , which had a striking decline of 1.01 GtC year −1 compared to the 2014–2023 average. The reduction in S LAND , most pronounced in tropical regions, contributed ~50% to the 2024 CGR increase—a larger impact than that of fossil fuel emissions or ocean sinks. Moreover, using partial least squares structural equation modelling, we further explained the underlying mechanism for the reduction of the S LAND in 2024, which was caused by hotter and drier conditions leading to a larger increase in respiration than photosynthesis. Our findings underscore the urgent need to investigate the mechanisms behind the declining carbon sink amid persistent global greening. These results challenge previous assumptions about the long‐term stability of the terrestrial carbon sink and highlight society's growing dependence on adaptive strategies to mitigate climate warming.

Optimization of friction medium rod shape and its enhanced pre-concentration of coal-hosted graphite ore by triboelectric separation - Yuhao Liu; Jingfeng He; Wenjie Tang; Shuaixing Shi; Lingtao Zhu; Bin Yang (Minerals Engineering, 2026)

Mechanical behaviour of axially-loaded reinforced CGCC columns: Testing and numerical modelling - Ziming Hu; Jingfeng Wang; Fengqin Wang; Zhenqing Shi; Zhenyu Hu (Engineering Structures, 2026)

Environmental DNA reveals shift in phytoplankton community driven by sewage-derived eutrophication in coastal waters - Jie Su; Xuexin Wu; Tingting Shi; Shanshan Dong; Daoyang Shi; Hanjun Chen; Hongxia Ming; Jingfeng Fan (Marine Environmental Research, 2026)

Mechanical Behavior and Fracture Evolution of Non-Persistent Rock Joints Using Digital Image Correlation - Xinggang Wang; Xin Jin; Shuaishuai Wang; Jingfeng Shi; Yong Xu; Shuqi Ma; Qilin Yan (Geotechnical and Geological Engineering, 2025)

3D printing of scaffolds for articular cartilage/osteochondral regeneration: Design, performance, and applications - Luhao Li; Guang Shi; Zijian Wu; Zhenxin Cai; Junwu Wang; Zhuowen Hao; Renxin Chen; Zhenzhou Piao; Chao Chen; Jingfeng Li (Chemical Engineering Journal, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Examining the impact of common faults on chiller performance through experimental investigation and parameter sensitivity analysis - Zhanwei Wang; Penghua Xia; Sai Zhou; Lin Wang; Jingjing Guo; Xiuzhen Li; Jingfeng Shi; Jianxing Chen (Energy and Buildings, 2024)

Promoting the denitrification process by heavy metals in Liaohe Estuary sediment - Ming Hongxia; Zan Shuaijun; Liu Jiwen; Su Jie; Ren Kaijia; Lin Jiannan; Chen Quanrui; Shi Yinyin; Shi Tingting; Fan Jingfeng (Marine Pollution Bulletin, 2024)

Significantly enhanced biodegradation of profenofos by Cupriavidus nantongensis X1T mediated by walnut shell biochar - Genrong Zhang; Jingfeng Xue; Yufei Zhang; Jia Ye; Nan Zhang; Liancheng Fang; Taozhong Shi; Xin Ma; Hui Li; Rimao Hua (Journal of Hazardous Materials, 2024)

Long-term response of the microbial community to the degradation of DOC released from Undaria pinnatifida - Yuyang Xie; Jie Su; Kuishuang Shao; Tian Hu; Hongxia Ming; Tingting Shi; Wenjing Wang; Jingfeng Fan (Marine Environmental Research, 2024)

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

Operation characteristics based on a novel performance model based on capacity utilization rate of a variable refrigerant flow air conditioning system - Hansong Xiao; Shurong Liu; Yunxiao Ding; Chunyuan Zheng; Bing Luo; Heng Niu; Jingfeng Shi; Baolong Wang; Qiang Song; Wenxing Shi (Energy and Buildings, 2023)

Experimental research on the performance and parameters sensitivity analysis of variable refrigerant flow system with common faults imposed in heating mode - Wei Gou; Zhaoting Ren; Huanxin Chen; Lu Xing; Zhenxin Zhou; Xingxiang Xia; Jingfeng Shi (Energy and Buildings, 2023)

Prevalence, antibiotic and heavy metal resistance of Vibrio spp. isolated from the clam Meretrix meretrix at different ages in Geligang, Liaohe estuary in China - Jie Su; Yingxue Zhang; Tian Hu; Hongxia Ming; Yuyang Xie; Yuan Jin; Tingting Shi; Jingfeng Fan (Frontiers in Marine Science, 2022)
Vibrio as one of the main pathogens of shellfish diseases can cause serious human seafoodborne gastroenteritis and even death. In this study, we analyzed the bacterial communities from the clam, and compared the resistance phenotypes and genotypes of Vibrio spp. from Meretrix meretrix at different growth stages. High-throughput sequencing analysis revealed the predominance of Proteobacteria (50%) in the bacterial community and Vibrio was one of the dominant genera in the clam hepatopancreas in the summer. Vibrio abundance in Meretrix meretrix positively correlated with the water temperature (p<0.05). A total of 73 Vibrio isolates from Meretrix meretrix were classified into 19 species and the dominant strains included V. mediterranei (19%) and V. harveyi (11%), V. algolyticus (10%), and V. parahaemolyticus (8%). The species and abundance of Vibrio spp. were the highest in the 3-year-old of Meretrix meretrix compared with clams of other ages in the summer. Among the 73 isolates, 68 Vibrio strains were resistant to other 15 antibiotics except for sulfamethoxazole-trimethoprim with 57 resistant phenotypes. The most prevalent resistance was toward clindamycin (76%), followed by amikacin (63%), ampicillin (62%), rifampicin (62%), vancomycin (57%), and amoxicillin (50%). The ARI values of Vibrio spp. in different ages ranged from 0.13 to 0.18, and ARI values of 3-year-old (ARI=0.18) clams are higher than that of other ages clam. Approximately 72% of the resistant isolates showed multidrug-resistant phenotypes with maximum resistance to 15 antibiotics. Tolerance to heavy metals including Cd, Zn, and Cu was detected in the majority of antibiotic resistant isolates. In addition to the co-resistance to the same class of antibiotics, resistance to cephalosporin (CFP, CEP, CZ) were significantly correlated with penicillins (AMP, AMC) ( p < 0.01), tetracycline ( p < 0.001), sulfanilamide (SXT) ( p < 0.01) and quinolone (CIP) ( p < 0.01). The heavy metal resistance genes copB and nccA were significantly correlated with the clindamycin resistance phenotype ( p <0.01). This study revealed that the habitat of Meretrix meretrix is in low exposure to antibiotics, and a link between heavy metal resistance genes and antibiotic resistance.

Aberrant interhemispheric functional connectivity in first-episode, drug-naïve major depressive disorder - Hong Yang; Chengwei Wang; Gongjun Ji; Zhan Feng; Jingfeng Duan; Feng Chen; Xiaohong Joe Zhou; Yushu Shi; Haiyan Xie (Brain Imaging and Behavior, 2019)

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary - Yongkai Chang; Jingfeng Fan; Jie Su; Hongxia Ming; Wen Zhao; Yan Shi; Fengyun Ji; Limei Guo; Shuaijun Zan; Bochao Li; Hao Guo; Daoming Guan (Current Microbiology, 2017)